Odpowiedzi

Najlepsza Odpowiedź!
2009-09-12T22:52:13+02:00
Oblicz wartość wyrażenia
a) ( pierwiastek z 5 + x)2 - (pierwiastek z 5 - x)2 dla x = pierwiastek z 5 - 1
b) x+1
----
x4 - 2
dla x równego - 1 - pierwiastek z 3

(√5+x)²-(√5-x)²= (√5+x+√5-x)(√5+x-√5+x)=2√5 × 2x=4√5x = 4√5(√5-1)=
20-4√5

x+1
--------= (-1-√3+1) / [(-1-√3)⁴-2] =(-√3) / [(1+2√3+3)(1+2√3+3)-2]=
x⁴ - 2

(-√3) / [(4+2√3)(4+2√3)-2]=(-√3) /(16+16√3+12-2)=(-√3) /(26+16√3)=
(-√3) (26-16√3) / (26+16√3)(26-16√3) =( -26√3+48) / (676-768) =
( -26√3+48) / (-92)= (13√3-24) / 46
1 5 1